Santiago Jiménez - Unsupervised Learning of Disentangled and Interpretable Representations of Material Appearance - Jiménez, Santiago (Jornada de Jóvenes Investigadores del I3A, 2024)
Unsupervised Learning of Disentangled and Interpretable Representations of Material Appearance